2020
DOI: 10.1007/s40820-020-00431-3
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Light-Responsive Nitric Oxide Delivery Platform for Enhanced Radioimmunotherapy

Abstract: HIGHLIGHTS • Ag 2 S NO delivery platforms maximize radiotherapy effects remarkably to inhibit the tumor growth. • Immunosuppressive tumor microenvironment was improved by Ag 2 S NO delivery system, significantly enhancing the anti-PD-L1 immune checkpoint blockade therapy. ABSTRACT Radiotherapy (RT) is a widely used way for cancer treatment. However, the efficiency of RT may come with various challenges such as low specificity, limitation by resistance, high dose and so on. Nitric oxide (NO) is known a very eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 60 publications
0
35
0
Order By: Relevance
“…However, NO-based combination therapy has been extensively studied. Current ● NO-based treatment research mainly focuses on four pathways, including high concentration-induced cytotoxicity [ 127 ], as a chemotherapy sensitizer [ 128 ], as radiation therapy sensitizer [ 129 ], or as phototherapy sensitizer [ 120 , 122 ]. The ever-increasing antitumor research about the combination of ● NO therapy with various therapeutic strategies demonstrated the great significance of summarizing the related research works.…”
Section: Reactive Nitrogen Species-mediated Tumor Suppressionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, NO-based combination therapy has been extensively studied. Current ● NO-based treatment research mainly focuses on four pathways, including high concentration-induced cytotoxicity [ 127 ], as a chemotherapy sensitizer [ 128 ], as radiation therapy sensitizer [ 129 ], or as phototherapy sensitizer [ 120 , 122 ]. The ever-increasing antitumor research about the combination of ● NO therapy with various therapeutic strategies demonstrated the great significance of summarizing the related research works.…”
Section: Reactive Nitrogen Species-mediated Tumor Suppressionmentioning
confidence: 99%
“…(c) The preparation of Ag 2 S@BSA-SNO for cancer therapy. Reprinted with permission [ 129 ]. Copyright 2020, Springer Nature.…”
Section: Reactive Nitrogen Species-mediated Tumor Suppressionmentioning
confidence: 99%
“…In recent years, photodynamic therapy “PDT” and photothermal therapy “PTT” and other phototherapy techniques have been increasingly studied in tumor treatment [76] . The photosensitizer used in photodynamic therapy can convert the oxygen in the tumor into singlet oxygen or reactive oxygen species (ROS) [77] . PTT is a non‐invasive strategy that used near‐infrared light and photothermal conversion agents to increase the temperature of the tumor area [78] .…”
Section: Combination Of Nanotechnology‐based Immune Checkpoint Blockimentioning
confidence: 99%
“…[76] The photosensitizer used in photodynamic therapy can convert the oxygen in the tumor into singlet oxygen or reactive oxygen species (ROS). [77] PTT is a non-invasive strategy that used near-infrared light and photothermal conversion agents to increase the temperature of the tumor area. [78] Both PDT and PTT can induce tumor vascular necrosis and cancer cell apoptosis.…”
Section: Phototherapymentioning
confidence: 99%
“…For instance, the chemicals used in traditional chemotherapy are difficult to penetrate into tumor centers and are prone to develop drug resistance (W. Han et al, 2018; Xie, Wan, Chen, Han, & Wang, 2020; Q. Zhou et al, 2018). Radiation therapy and surgical treatment might induce serious adverse effects to normal cells/tissues and promote tumor metastasis (Chen et al, 2018; Shu et al, 2020; X. Zhou et al, 2020). Therefore, novel cancer therapies with higher therapeutic efficacy to cancer cells/tissues and lower toxicity to normal cells/tissues are still being developed.…”
Section: Introductionmentioning
confidence: 99%